2012
DOI: 10.1016/j.cell.2012.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Transport Organize Microtubules in Metaphase Spindles

Abstract: Spindles are arrays of microtubules that segregate chromosomes during cell division. It has been difficult to validate models of spindle assembly due to a lack of information on the organization of microtubules in these structures. Here we present a method, based on femtosecond laser ablation, capable of measuring the detailed architecture of spindles. We used this method to study the metaphase spindle in Xenopus laevis egg extracts and found that microtubules are shortest near poles and become progressively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
195
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(214 citation statements)
references
References 55 publications
14
195
2
Order By: Relevance
“…By comparing the two waves, information about the polarity of MTs could be obtained, and irradiating different regions of the spindle showed that MTs were longer near the center of the spindle and shorter toward the poles. Interestingly, inhibition of poleward MT flux homogenized spindle MT lengths, supporting a model in which spindle architecture depends on both the position of MT nucleation near the center of the spindle and poleward MT transport (Brugues et al, 2012).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…By comparing the two waves, information about the polarity of MTs could be obtained, and irradiating different regions of the spindle showed that MTs were longer near the center of the spindle and shorter toward the poles. Interestingly, inhibition of poleward MT flux homogenized spindle MT lengths, supporting a model in which spindle architecture depends on both the position of MT nucleation near the center of the spindle and poleward MT transport (Brugues et al, 2012).…”
mentioning
confidence: 77%
“…Perhaps more interestingly, tubulin lifetime measurements did not vary across different regions of the spindle, suggesting that despite specific localization of factors that alter MT dynamics within the spindle, overall MT stability is uniform. Further support for a model of spindle organization with homogenous MT stability in all regions stems from using a femtosecond laser ablation technique to cut a subset of MTs within a metaphase Xenopus egg extract spindle (Brugues et al, 2012;Fig. 3.3D).…”
mentioning
confidence: 99%
“…4b), indicating that the majority of minus-ends of microtubules in C. elegans spindles are located at the centrosomes, whereas plus-ends grow towards the chromosomes. We challenged this finding by performing laser microsurgery to ablate microtubules within the spindle and so measure their polarity by generating new microtubule plus-and minus-ends 24 . Microsurgery resulted in the formation of a single wave of depolymerization of the newly created microtubule plus-ends towards the centrosome (Supplementary Movie 4).…”
Section: Resultsmentioning
confidence: 99%
“…While light microscopy provides a dynamic picture of the spindle 15,[22][23][24] , it cannot resolve individual microtubules. Electron microscopy overcomes this limitation though, until now, little quantitative data on the fine structure of mitotic spindles has been published.…”
mentioning
confidence: 99%
“…The spatial distribution of microtubule nucleation is key for understanding size and architecture of large spindles. This is because microtubules in these spindles are short and turnover rapidly (3,10,11). The mechanisms underlying the spatial regulation of microtubule nucleation, however, are still unclear (12, 13).…”
Section: Main Textmentioning
confidence: 99%